2012
DOI: 10.3402/tellusb.v64i0.17134
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale spatial variability of major ions in the atmospheric wet deposition along the China–Antarctica transect (31°N–69°S)

Abstract: A B S T R A C T Twenty-two atmospheric wet deposition samples were collected along the large-scale transect from China to Antarctica, and the major ion components as well as their sources were analysed. It is the first time that chemical composition variation of precipitation has been investigated on such a large-scale transect. The results show that the precipitations exhibit near-neutral pH on the average. On the whole, ionic levels on an equivalent basis are presented as Cl ( , and ionic contents of rainfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
(21 reference statements)
2
21
0
Order By: Relevance
“…Details on this method are described in Shi et al (2012). Details on this method are described in Shi et al (2012).…”
Section: Sample Analysis 221 Ion Chemistry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Details on this method are described in Shi et al (2012). Details on this method are described in Shi et al (2012).…”
Section: Sample Analysis 221 Ion Chemistry Analysismentioning
confidence: 99%
“…In the laboratory, analyses of major ions (Na + , NH 4 + , K + , Mg 2+ , Ca 2+ , Cl − , NO 3 − , and SO 4 2− ) were performed using a Dionex ICS-3000 ion chromatograph. Details on this method are described in Shi et al (2012). Repeated measurements within and across different runs were conducted to check the analysis precision.…”
Section: Sample Analysis 221 Ion Chemistry Analysismentioning
confidence: 99%
“…Significant losses can account for NO − 3 profiles at inland sites, i.e., NO − 3 concentration decreasing with increasing depths. Previous observations and modeling works suggested that photolysis dominates the losses Erbland et al, 2013;Shi et al, 2015). During photolysis of NO − 3 , some of the photoproducts (NO x ) are emitted into the gas phase France et al, 2011), and these products could undergo reoxidation by the local oxidants (e.g., hydroxyl radical (OH), NO 2 + OH + M → HNO 3 + M), forming gas-phase HNO 3 .…”
Section: No − 3 In Inland Snowpackmentioning
confidence: 99%
“…Gas-phase and snow concentration studies and recent isotopic investigations and modeling have shown that NO − 3 , particularly in snow on the Antarctic plateau, is a combination of deposition of HNO 3 and post-depositional loss or recycling of NO − 3 (e.g., Röthlisberger et al, 2002;Davis et al, 2004;Dibb et al, 2004;Erbland et al, 2013Erbland et al, , 2015Shi et al, 2015;Bock et al, 2016;Zatko et al, 2016). Based upon a suite of isotopic studies in the field and laboratory, it has been demonstrated that under cold, sunlit conditions ultraviolet photolysis dominates NO − 3 post-depositional processing, whereas HNO 3 volatilization may become more important at warmer temperatures > −20 • C (Röthlisberger et al, 2002;Frey et al, 2009;Erbland et al, 2013;Berhanu et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation